A checklist of Iranian Deltocephalinae (Hemiptera: Cicadellidae) - Farzad Pakarpour Rayeni; Jamasb Nozari; Ali Asghar Seraj (Iranian Journal of Animal Biosystematics, 2015)
By using published records and original data from recent research, the first checklist for subfamily Deltocephalinae from Iran is presented. This study is based on a comprehensive review of literature and the examination of some materials from our collection. The present checklist contains 185 species belonging to 74 genera. In addition for each species, the known geographical distribution in Iran and in the world is reported.